Landmarks of identity: Bronze Age towers of the Oman Peninsula - Döpper, Stephanie (Ministry of Heritage and Tourism, Sultanate of Oman, 2024)
In the Early Bronze Age, monumental stone and mud-brick structures known as towers appeared in Oman. This book updates the long-standing discussions on these towers and to assess their chronological depth of more than a millennium. It also reassesses their possible functions in the light of recent archaeological research
Keywords: Oman -- Antiquities